Projeto de ponte rolante - Campos, Antonia Paloma Matias (Universidade Federal Rural do Semi-Árido, 2018)
The crane is the most efficient system for locomotion of heavy loads both at small and large distances, but some limitations due to the pendulum movement of the load make difficult the precise positioning of the same. A crane is a mobile lifting device that can move on a moving path in which it designates a path through rolling in its tracks. The purpose of this work is to develop the basic design of a crane. In order to achieve this objective, specific standards will be used for such project. In this way, the methodology applied to the development of this project will follow step by step the recommendations proposed by the standards, and through researches, we can adopt the values for load lifting capacity, lifting height, bridge weight, span of the crane, among others , taking into account the application of it. It is expected at the end of this study to obtain a basic design of a crane with capacity to meet predetermined specifications.
Monografia
Keywords: Ponte rolante; Dimensionamento; Carga; Componentes; Estrutura; Crane; Scaling; Charge; Components; Structure; ENGENHARIAS::ENGENHARIA MECANICA